Novel Zn(ii)-thiazolone-based solid fluorescent chemosensors: naked-eye detection for acid/base and toluene. Issue 57 (31st May 2016) - Lin, Xu-Dong; Peng, Biao; Li, Shao-Yong; Shao, Jia; Li, Qing-Zhong; Xie, Cheng-Zhi; Xu, Jing-Yuan
Abstract : Three zinc complexes with diverse ligand's substituents show interesting fluorescence switching properties induced by acid/base vapour or toluene. Abstract : A series of novel thiazolone-based zinc complexes, [Zn(Am4DHotaz)Cl2 ]·H2 O (1 ), [Zn(Am4Motaz)Cl2 ] (2 ), and [Zn(Am4Eotaz)Cl2 ] (3 ) (Am4DHotaz = N -(4-oxothiazolidin-2-ylidene)picolinohydrazonamide, Am4Motaz = N -(3-methyl-4-oxothiazolidin-2-ylidene)picolinohydrazonamide, Am4Eotaz = N -(3-ethyl-4-oxothiazolidin-2-ylidene)picolinohydrazonamide), with intense fluorescence emission and large Stokes shifts in the solid state, have been synthesized and characterized by X-ray crystallography and various spectroscopic methods. Complexes1–3 exhibit a similar Zn 2+ -coordinated pattern, but different molecular packings arising from substituent variation in the organic ligands, which finally result in individual fluorescent behaviors. All the complexes showed interesting ON/OFF/ON fluorescence switching properties induced by acid/base vapor. More interestingly, for1, the introduction of toluene brought about a large blue shift, an obvious color change suitable for naked-eye detection, and a distinct increase of fluorescent quantum yield, which could contribute to environmental monitoring and other applications in the field of luminescent materials.